Even Number Boards In Indonesian Companies - David, Martha; Juliana, Rita (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2020)
The recent globalization has forced firms throughout the world to enhance the performance. The aim of this research is to prove that corporate boards with even number of directors have inadequate corporate governance activities, to prove that corporate boards with even number of directors have inadequate agency problems and to prove that corporate boards with even number of directors decreases firm value, measured by meetings, expenses and market value of equity. The data is collected from the annual financial reports of 197 companies in 2013-2017 period, with a total of 985 company-year observations. The analysis is conducted using panel data regression method after going through diagnostic test. The results of this analysis show that even number of directors does impact corporate governance activities, causes inadequate agency problems and affects firm value. Firms with even number of boards is found having less meeting, greater expenses and lower market value of equity.